Una Resurrezione del Maestro delle Ore Tocco al Brooklyn Museum: sulle tracce dei corali quattrocenteschi di San Domenico Maggiore a Napoli - D'Urso, Teresa (2018)
This artide draws attention to a little known illuminated folio representing the Resurrection of Christ (New York, Brooklyn Museum) and an unpublished Dominican gradua/-sanctoral (Naples, Biblioteca del Convento di San Domenico Maggiore, cor. 20). An analysis of style and iconography locates the production of both works in Naples over the course of the end of the Quattrocento and the first years of the Cinquecento. In fact, the works bear evidence of the stylistic legacy of Giovanni Todeschino, an illuminator from Bergamo active in the capital of the Regno between the 1480s and 1503. Recognized for the first time in the Resurrection is the hand of the so-called Master of the Tocco Hours, alias Vincenzo Borsano, the greatest of Todeschino's followers; and identified in the historiated initial of San Domenico in the gradual-sanctoral is the hand of another illuminator influenced by the Bergamese artist. Further, the folio with the Resurrection is shown to have formed part of a gradual for the Easter season, and, as in the case of the gradual-santoral stili conserved today at San Domenico Maggiore, is hypothesized to have been made for that same Neapolitan monastery. The article then proceeds to discern substantial interventions in the illuminated decoration of the Resurrection folio, both in the text's incipit and in the musical notation. An analysis of the folio's physical condition leads to the hypothesis that these passages were reworked in the later nineteenth century to conceal lacunae and damages when the leaf appeared on the antiquarian market. The Brooklyn Museum's Resurrection folio is thus important evidence of the dispersal of the libraries of several Neapolitan religious communities in the ninteenth century, and together with the San Domenico gradual-sanctoral opens a new avenue of research into late Quattrocento choirbooks from San Domenico, unti now lost without a trace.